Black Phosphorous Mediates Surface Charge Redistribution of CoSe2 for Electrochemical H2O2 Production in Acidic Electrolytes. Issue 43 (28th September 2022) - Zheng, Ya‐Rong; Hu, ShaoJin; Zhang, Xiao‐Long; Ju, Huanxin; Wang, Zhenbin; Tan, Peng‐Ju; Wu, Rui; Gao, Fei‐Yue; Zhuang, Taotao; Zheng, Xiao; Zhu, Junfa; Gao, Min‐Rui; et al.
Abstract: Electrochemical generation of hydrogen peroxide (H2 O2 ) by two‐electron oxygen reduction offers a green method to mitigate the current dependence on the energy‐intensive anthraquinone process, promising its on‐site applications. Unfortunately, in alkaline environments, H2 O2 is not stable and undergoes rapid decomposition. Making H2 O2 in acidic electrolytes can prevent its decomposition, but choices of active, stable, and selective electrocatalysts are significantly limited. Here, the selective and efficient two‐electron reduction of oxygen toward H2 O2 in acid by a composite catalyst that is composed of black phosphorus (BP) nailed chemically on the metallic cobalt diselenide (CoSe2 ) surface is reported. It is found that this catalyst exhibits a 91% Faradic efficiency for H2 O2 product at an overpotential of 300 mV. Moreover, it can mediate oxygen to H2 O2 with a high production rate of ≈1530 mg L −1 h −1 cm −2 in a flow‐cell reactor. Spectroscopic and computational studies together uncover a BP‐induced surface charge redistribution in CoSe2, which leads to a favorable surface electronic structure that weakens the HOO* adsorption, thus enhancing the kinetics toward H2 O2 formation. Abstract : Black phosphorus chemically nailed on metallic cobalt diselenide mediates surface charge redistribution, which enables a selective and efficient two‐electron reduction of oxygen toward hydrogen peroxide (H2 O2 ) in acid. The catalyst exhibits a 91% Faradic efficiency for H2 O2 at an overpotential of 300 mV, and a high production rate of ≈1530 mg L −1 h −1 cm −2 in a flow‐cell reactor.